Prognostic Scoring System Predictive of Survival after Surgical Resection of Esophageal Carcinoma - Gockel, Ines; Niebisch, Stefan; Campbell, Lynetta K.; Sgourakis, George; Junginger, Theodor (The Thoracic and Cardiovascular Surgeon, 2013)
Background The aim of our study was to develop a prognostic index score for patients undergoing surgical resection for esophageal cancer that accurately determines survival with specific clinicopathological characteristics.Methods Clinical, histological, and demographical variables of 475 patients were entered in an univariate and multivariate regression model, followed by individual calculation of the Prognostic Indicator Score and model validation via simulation.Results Significant variables included in the scoring system were number of positive lymph nodes, pT, pL, R, obesity, and American Society of Anesthesiologist classification. Survival probability and its associated hazard function was significantly different between the scores, with an increase of hazard ratio ranging from 2.56 (score 2) to 20 (score 6 or higher). Comparing histological cancer entities revealed statistical significance only between stage IIA versus IIB in squamous cell and stage IIIA versus IIIB in adenocarcinoma.Conclusions According to our methodology, an individualized follow-up by each possible score might allow interdisciplinary selection of patients for treatments based on expected survival. This may represent a breakthrough in patient selection for currently available treatments and clinical studies.
Keywords: prognostic index score; esophageal cancer; surgical approach; operative; computing methodologies; model validation